Memória de reconhecimento em indivíduos adultos com mais de 45 anos - Bezerra, Yalkirira Guadalupe Vaca Diaz (2006)
As we grow old, there are many cognitive processes which decline in the human brain. One of them is the memory, a function that allows retention and posterior use of knowledge learned during the life, understood as a result of multiple systems highly organized and spread in several neural regions. This work aimed to evaluate the recognition memory in adults over 45 years old through words and pictures recognition tasks and the use of two codification or learning conditions (same distracters and different distracters). Twelve individuals were studied (6 men and 6 women) aged between 45 and 88 years old and with similar demographic characteristics. They presented better performance on picture tasks rather than word tasks. Better results were also verified when the codification context had different distracters, which significantly reflected in a long term principally in elderly individuals. The results reached suggest that the codification context influenced the lists of pictures and words learning, mainly for the elderly ones, when compared to adults, and that these results can be related to the phenomena involved with the recognition memory, the recollection and familiarity